Glial diffusion barriers during aging and pathological states - Syková, E (Progress in brain research, 2001)
In conclusion, glial cells control not only ECS ionic composition, but also ECS size and geometry. Since ECS ionic and volume changes have been shown to play an important role in modulating the complex synaptic and extrasynaptic signal transmission in the CNS, glial cells may thus affect neuronal interaction, synchronization and neuron-glia communication. As shown in Fig. 2, a link between ionic and volume changes and signal transmission has been proposed as a model for the non-specific feedback mechanism suppressing neuronal activity (Syková, 1997; Ransom, 2000). First, neuronal activity results in the accumulation of [K+]e, which in turn depolarizes glial cells, and this depolarization induces an alkaline shift in glial pHi. Second, the glial cells extrude acid and the resulting acid shift causes a decrease in the neuronal excitability. Because ionic transmembrane shifts are always accompanied by water, this feedback mechanism is amplified by activity-related glial swelling compensated for by ECS volume shrinkage and by increased tortuosity, presumably by the crowding of molecules of the ECS matrix and/or by the swelling of fine glial processes. This, in turn, results in a larger accumulation of ions and other neuroactive substances in the brain due to increased diffusion hinderance in the ECS. Astrocyte hypertrophy, proliferation and swelling influence the size of the ECS volume and tortuosity around neurons, slowing diffusion in the ECS. Their organization may also affect diffusion anisotropy, which could be an underlying mechanism for the specificity of extrasynaptic transmission, including 'cross-talk' between distinct synapses (Barbour and Hausser, 1997; Kullmann and Asztely, 1998). An increased concentration of transmitter released into a synapse (e.g. repetitive adequate stimuli or during high frequency electrical stimulation which induces LTP) results in a significant activation of high-affinity receptors at neighboring synapses. The efficacy of such synaptic cross-talk would be dependent on the extracellular space surrounding the synapses, i.e. on intersynaptic geometry and diffusion parameters. Other recent studies have also suggested an important role for proteoglycans, known to participate in multiple cellular processes, such as axonal outgrowth, axonal branching and synaptogenesis (Hardington and Fosang, 1992; Margolis and Margolis, 1993) that are important for the formation of memory traces. Recent observation of a decrease of fibronectin and chondroitin sulfate proteoglycan staining in the hippocampus of behaviorally impaired aged rats (Syková et al., 1998a,b) supports this hypothesis. It is reasonable to assume that besides neuronal and glial processes, macromolecules of the extracellular matrix contribute to diffusion barriers in the ECS. It is therefore apparent that glial cells play an important role in the local architecture of the CNS and they may also be involved in the modulation of signal transmission, in plastic changes, LTP, LTD and in changes of behavior and memory formation.
Keywords: homeostáza; Anisotropy; Aging; Diffusion; Astrocytes; Homeostasis; difuze; Nervous System Diseases; nemoci nervového systému; extracelulární matrix; Nerve Tissue; Animals; extracelulární prostor; nervová tkáň; Extracellular Space; anizotropie; zvířata; Extracellular Matrix; stárnutí; neuroglie; Neuroglia; astrocyty